If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3(q-4)+12=7(q+2)
We move all terms to the left:
-3(q-4)+12-(7(q+2))=0
We multiply parentheses
-3q-(7(q+2))+12+12=0
We calculate terms in parentheses: -(7(q+2)), so:We add all the numbers together, and all the variables
7(q+2)
We multiply parentheses
7q+14
Back to the equation:
-(7q+14)
-3q-(7q+14)+24=0
We get rid of parentheses
-3q-7q-14+24=0
We add all the numbers together, and all the variables
-10q+10=0
We move all terms containing q to the left, all other terms to the right
-10q=-10
q=-10/-10
q=1
| -12=s-20 | | 5j-3=7 | | 3(x+6)=4x-7 | | 7x–5=3x–1 | | 6x+7(-5x+20)=-5 | | 3x+2(-4)=32 | | 10+z=-26 | | 19+8j=3 | | 0.5x=(4x-6)21 | | 11y+6=6 | | 2(x-5)+4(x+1)=18 | | Y=5x(15,-3) | | 9^3x−10=(181)^16 | | 5x+9=14x+4 | | -0.5-3.3=x | | 2.4+5.1x=9+5.1x | | -10-7j=-8j | | 0.5x=4x-6=21 | | z/32=2 | | 3x+29+4x-9=180 | | -x+12=-24 | | 8+16y=6 | | 6y+20-4y=-7y+56 | | (2x-3=2)+(3x+8=-2) | | 13y-1=12 | | .5x-4=11 | | 2.9=f+4.3 | | 0.2(x+2)-22=-x | | 4x–1x+7=-53 | | 15y-12y+-11y-5=19 | | 6x+7(-5+20)=-5 | | (x-4)(x+7)=x^2-4 |